2017
DOI: 10.1371/journal.pone.0181932
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the permeability barrier and peptidoglycan recycling pathways to disarm Pseudomonas aeruginosa against the innate immune system

Abstract: Antimicrobial resistance is a continuously increasing threat that severely compromises our antibiotic arsenal and causes thousands of deaths due to hospital-acquired infections by pathogens such as Pseudomonas aeruginosa, situation further aggravated by the limited development of new antibiotics. Thus, alternative strategies such as those targeting bacterial resistance mechanisms, virulence or potentiating the activity of our immune system resources are urgently needed. We have recently shown that mutations si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 70 publications
(127 reference statements)
5
50
0
Order By: Relevance
“…Further, the analysis of a set of P. aeruginosa mutants very similar to those used in the above-mentioned work by Pérez-Gallego and colleagues (223) has recently revealed that, besides fitness and virulence attenuation, PGN recycling impairment (together or not with AmpC derepression) determines a great increase in bacterial susceptibility to innate immune weapons targeting the PGN, such as lysozyme and the four human PGN recognition proteins (PGRPs) (203). Lysozyme (also known as muramidase or N-acetylmuramide glycanhydrolase) is especially abundant in secretions and in neutrophil granules and catalyzes the hydrolysis of 1,4-beta linkages between NAcMur and NAcGlc.…”
Section: Interplay Among ␤-Lactamase Production Peptidoglycan Recyclmentioning
confidence: 98%
See 2 more Smart Citations
“…Further, the analysis of a set of P. aeruginosa mutants very similar to those used in the above-mentioned work by Pérez-Gallego and colleagues (223) has recently revealed that, besides fitness and virulence attenuation, PGN recycling impairment (together or not with AmpC derepression) determines a great increase in bacterial susceptibility to innate immune weapons targeting the PGN, such as lysozyme and the four human PGN recognition proteins (PGRPs) (203). Lysozyme (also known as muramidase or N-acetylmuramide glycanhydrolase) is especially abundant in secretions and in neutrophil granules and catalyzes the hydrolysis of 1,4-beta linkages between NAcMur and NAcGlc.…”
Section: Interplay Among ␤-Lactamase Production Peptidoglycan Recyclmentioning
confidence: 98%
“…First, it is worth mentioning that some works have suggested that the muramidase activity of lysozyme is not necessary for its bactericidal power, since it displays membrane permeabilization action, therefore actually working as a cationic peptide (198,(200)(201)(202). Additionally, it has to be stated that many works have proposed that lysozyme generally has low activity per se against Gram-negative bacteria, unless the outer membrane is permeabilized by some other innate immune compound (198,203). However, different bacterial inhibitors of the three types of lysozyme that exist in the animal kingdom (chicken or conventional [c-type], goose [g-type], and invertebrate [i-type] lysozymes) have been described (204).…”
Section: Lysozyme Inhibitors: Targets To Increase the Activity Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…A credible strategy to create meaningful clinical adjuvants to preserve β‐lactam efficacy would be to suppress muropeptide recycling in its entirety. Indeed, preliminary data support fully this hypothesis . One focus of such an effort would be the understanding of the enigmatic functions of the LT family and the respective means to their regulation .…”
Section: Abetting the β‐Lactam Antibiotics Against Gram‐negative Bactmentioning
confidence: 91%
“…Indeed, preliminary data support fully this hypothesis. [280][281][282] One focus of such an effort would be the understanding of the enigmatic functions of the LT family and the respective means to their regulation. 283,284 Accordingly, we have undertaken extensive mechanistic and structural studies of this family.…”
Section: Abetting the β-Lactam Antibiotics Against Gram-negative Bamentioning
confidence: 99%